2017
DOI: 10.1038/ncomms14646
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Rab-coupling protein by LMTK3 controls Rab14-dependent EphA2 trafficking to promote cell:cell repulsion

Abstract: The Rab GTPase effector, Rab-coupling protein (RCP) is known to promote invasive behaviour in vitro by controlling integrin and receptor tyrosine kinase (RTK) trafficking, but how RCP influences metastasis in vivo is unclear. Here we identify an RTK of the Eph family, EphA2, to be a cargo of an RCP-regulated endocytic pathway which controls cell:cell repulsion and metastasis in vivo. Phosphorylation of RCP at Ser435 by Lemur tyrosine kinase-3 (LMTK3) and of EphA2 at Ser897 by Akt are both necessary to promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 40 publications
(50 reference statements)
2
50
0
Order By: Relevance
“…Notably, FHOD3 knockdown does not impact on migration on 2D surfaces, but suppresses filopodial‐driven invasion in cell‐derived 3D matrix and 3D hydrogels . EphA2 is also a cargo of RCP, in this case directed by Rab14, and this trafficking pathway controls invasion and metastasis in pancreatic cancer (Figure ). Additionally, hepatocyte growth factor (HGF) stimulation leads to co‐internalization of c‐Met (HFGR) and β1 integrin, and is required for downstream signalling in a variety of cell types, and indeed c‐Met can follow a RCP‐α5β1 recycling route to promote cancer cell invasion (Figure ).…”
Section: Rtk Trafficking and Signalling In Cell Migrationmentioning
confidence: 99%
“…Notably, FHOD3 knockdown does not impact on migration on 2D surfaces, but suppresses filopodial‐driven invasion in cell‐derived 3D matrix and 3D hydrogels . EphA2 is also a cargo of RCP, in this case directed by Rab14, and this trafficking pathway controls invasion and metastasis in pancreatic cancer (Figure ). Additionally, hepatocyte growth factor (HGF) stimulation leads to co‐internalization of c‐Met (HFGR) and β1 integrin, and is required for downstream signalling in a variety of cell types, and indeed c‐Met can follow a RCP‐α5β1 recycling route to promote cancer cell invasion (Figure ).…”
Section: Rtk Trafficking and Signalling In Cell Migrationmentioning
confidence: 99%
“…52) They showed that EphA2 was constitutively internal- ized and returned to the cell membrane rapidly. However, upon hepatocyte growth factor (HGF) stimulation, the AktEphA2 pathway as well as the LMTK3-RCP pathway was activated.…”
Section: Cell Motility and Cell Morphologymentioning
confidence: 99%
“…Both the LMTK3-RCP signaling pathway and Akt-EphA2 signaling pathway were necessary for efficient invasion and metastasis in an in vivo model of pancreatic cancer. 52) It is well known that the Rho family of small GTPases plays critical roles in the regulation of cell motility and morphology. [53][54][55] Kawai et al 56) demonstrated that the interaction of EphA2 and Ephexin4, which is one of the RhoG guanine nucleotide exchanges, was induced in an EphA2 Ser-897 phosphorylation-dependent manner.…”
Section: Cell Motility and Cell Morphologymentioning
confidence: 99%
“…What drives formation of Rab14/MACF2/CAMSAP3 complex during telophase, but blocks it from functioning in metaphase and anaphase? Interesting, Rab14 was also implicated in regulating epithelial cell polarity (Lu and Wilson 2016), as well as recycling of integrins during cell migration (Gundry et al, 2017). Both of these cellular processes are also dependent on actin and microtubule dynamics, thus, it will be interesting to see whether Rab14 interaction with MACF2/CAMSAP3 complex may have functions during cell polarization and migration.…”
Section: Discussionmentioning
confidence: 99%